When back doors backfire. (Economist, 2016)
The article examines the use of back doors in encryption software by spy agencies as of January 2016. It states that spy agencies use back doors or the flaws in software or hardware to identify threats to national security, however they can also be used by criminals. The author comments that governments must resist calls for mandatory back door inclusion as it undermines confidence in technology firms and make the Internet more vulnerable to attacks.